Green HR practices An analytical study of the opinions of a sample of tourism workers in the holy city of Karbala (The Peerian Journal, 2023)
The study aimed to reveal the employment of green human resource practices in promoting sustainable competitive advantage, as green human resource management is one of the modern concepts in management that focuses on integrating green management concepts into human resource strategies, and helps to integrate environmental goals and strategies into sustainable development goals to reach To an effective environment management system to achieve several different advantages that benefit tourism companies, and the research dealt with the concept of human resource management, and a set of jobs that achieve sustainability, in addition to defining the competitive advantage and its dimensions, and the study population consisted of workers in tourism companies in the holy city of Karbala, and the study used the random sample method The study results showed that there are statistically significant differences between the opinions of workers in tourism companies in the holy city of Karbala about the role of green human resource practices in promoting sustainable competitive advantage. The study recommended developing green leadership methods and training leaders and managers on Going green with tourism companies. The participation of green human resources in tourism companies in activities related to improving the environment. Developing a comprehensive plan to implement green human resource management practices